The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/fcsr.12195
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Value of College as an Investment in Human and Social Capital: Views of Generations X and Y

Abstract: This article examines the perception of college based on the investment in human or social capital. An online survey was used to collect data. After deleting the responses from older cohorts (Baby Boomers and the Silent Generation) and incomplete responses, the sample consisted of 1,000 adult participants who had student loans. Similarities and differences between generations X and Y student loan borrowers were investigated. Generation Y ranked social capital reasons for a college education higher than human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Cultural capital, also called human capital, is knowledge that guides individuals or groups through society and affects interactions with others, judgment by others, and opportunities available [6,8,9,10]. Cultural capital takes the form of material goods (e.g., books, “proper” clothing) and symbolic elements (e.g., knowledge of societal customs, manners, and values; skill set; formal education credentials; socialization to express society’s valued attitudes and behaviors) that are admired and rewarded by society (e.g., college degree, slenderness).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural capital, also called human capital, is knowledge that guides individuals or groups through society and affects interactions with others, judgment by others, and opportunities available [6,8,9,10]. Cultural capital takes the form of material goods (e.g., books, “proper” clothing) and symbolic elements (e.g., knowledge of societal customs, manners, and values; skill set; formal education credentials; socialization to express society’s valued attitudes and behaviors) that are admired and rewarded by society (e.g., college degree, slenderness).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown generational differences in career patterns [35] and expectations from education [31,81], but few studies have examined how parents from differing generations (i.e., Generation X vs Millennials) who both have children of the same age group (i.e., preschoolers) differ. The findings of this study reveal that Generation X mothers were more educated than Millennial mothers, which is not surprising as Millennial mothers are younger and might continue their education at a later age for a workplace advancement or salary increase [32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Generation X witnessed a shift in communication tools whereas Millennials grew up surrounded by modern technology and the Internet [30]. Millennial students tend to value college education for its extrinsic or social capital benefits, such as for making more money or meeting new friends, whereas Generation X students tend to value intrinsic benefits, such as the appreciation of knowledge [31,32]. Millennials also are more individualistic, less altruistic at work [33,34], and experience greater job mobility than previous generations [35].…”
Section: Introductionmentioning
confidence: 99%
“…Research on residential satisfaction has applications within the student housing environment. This is a factor that newer generations of college students value more highly than students from previous generations (Johnson, Gutter, Xu, Cho, & DeVaney, 2016). These included such aspects as noise from nearby neighbors and clamor from periodic maintenance.…”
Section: Residential Satisfactionmentioning
confidence: 99%
“…Still, higher density provides opportunities for more social interactions among students and more opportunities for building social capital. This is a factor that newer generations of college students value more highly than students from previous generations (Johnson, Gutter, Xu, Cho, & DeVaney, 2016).…”
Section: Residential Satisfactionmentioning
confidence: 99%